2018
DOI: 10.1016/j.ajog.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based national guidelines for the management of suspected fetal growth restriction: comparison, consensus, and controversy

Abstract: Small for gestational age is usually defined as an infant with a birthweight <10th centile for a population or customized standard. Fetal growth restriction refers to a fetus that has failed to reach its biological growth potential because of placental dysfunction. Small-for-gestational-age babies make up 28-45% of nonanomalous stillbirths, and have a higher chance of neurodevelopmental delay, childhood and adult obesity, and metabolic disease. The majority of small-for-gestational-age babies are not recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
312
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(342 citation statements)
references
References 95 publications
4
312
0
10
Order By: Relevance
“…Several studies have reported, first, how best to monitor and deliver SGA neonates, second, that about 85% of SGA neonates are born at ≥ 37 weeks' gestation and, third, that the best prediction of a SGA neonate is achieved by routine ultrasound examination at 36 weeks' gestation. The findings of this study have highlighted the necessity to improve the performance of the 36‐week assessment in the prediction of both delivery of a SGA neonate and adverse perinatal outcome, and have demonstrated that these goals cannot be achieved by addition of fetal growth velocity between 32 and 36 weeks' gestation to EFW at 36 weeks.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have reported, first, how best to monitor and deliver SGA neonates, second, that about 85% of SGA neonates are born at ≥ 37 weeks' gestation and, third, that the best prediction of a SGA neonate is achieved by routine ultrasound examination at 36 weeks' gestation. The findings of this study have highlighted the necessity to improve the performance of the 36‐week assessment in the prediction of both delivery of a SGA neonate and adverse perinatal outcome, and have demonstrated that these goals cannot be achieved by addition of fetal growth velocity between 32 and 36 weeks' gestation to EFW at 36 weeks.…”
Section: Discussionmentioning
confidence: 82%
“…Fetal Growth Restriction (FGR), also known as Intra‐uterine Growth Restriction (IUGR), is a condition that classically was defined as an inappropriate fetal weight gain for a specific gestational age, or synonymously, as the impossibility to reach the fetal biological growth potential. Practically, FGR is demonstrated by the statistical deviation of an estimated fetal weight (EFW) or an abdominal circumference (AC) from a population‐based reference, with a typical threshold at the 10th, fifth or third centile. However, according to a recent expert consensus, this condition should be redefined and be restricted to the smallest fetuses, those with an EFW or an AC below the third centile, or impaired growth velocity, or alternatively to fetuses with an EFW below the 10th centile and a concomitant abnormal fetal or uterine Doppler.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Delphi survey of experts defined late FGR (≥ 32 weeks) in the presence of at least two of: (1) abdominal circumference (AC) or estimated fetal weight (EFW) < 10 th centile, (2) AC/EFW crossing centiles of more than two quartiles on non‐customized growth charts, and (3) CPR < 5 th or UA‐PI > 95 th centile. Indeed, some professional bodies now incorporate consideration of the CPR when making decisions regarding appropriate surveillance and/or timing of birth in late‐onset small‐for‐gestational age (SGA) or FGR cases, as it is believed to be a better test for predicting adverse perinatal outcome than its individual UA and MCA Doppler components.…”
mentioning
confidence: 99%
“…The management of late SGA/FGR is already covered by comprehensive recent reviews and protocols from various professional bodies, which include clear recommendations of the appropriate frequency of monitoring and timing of birth (summarized by McCowan et al …”
mentioning
confidence: 99%